1970
DOI: 10.3329/jbs.v14i0.436
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response of <i>Dinarmus basalis</i> (Rond.) (Hymenoptera: Pteromalidae) Parasitizing <i>Callosobruchus maculatus</i> (F.)

Abstract: The functional response of the parasitoid Dinarmus basalis (Rond.) (Hymenoptera: Pteromalidae) is determined to evaluate its potential as a biological control agent. Four female wasps in the presence of males parasitoids, were allowed to oviposit during their life span or hosts at different densities. The data were fit by Rogers′ (1972) parasitoid model. The rate of parasitoid search was a′= 0.123 ±0.005 life span -1 , and handling time Th = 0.056 ± 0.002 life span -1 . Volume of grain had no significant (P>0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…field conditions). Even in the laboratory, the functional response of a parasitoid is affected by many factors such as size of experimental arena, tested densities, time duration of experiments, distribution of hosts, the possibility of searching parasitoids to leave the experimental units and number of parasitoids searching together (Islam et al 2006). Moreover, the foraging behaviour under field conditions is determined by many other factors namely host patch accessibility or distribution, presence of competitors and temperature (Fernández-arhex and Corley 2003;Luna et al 2007).…”
Section: Host Densitymentioning
confidence: 99%
“…field conditions). Even in the laboratory, the functional response of a parasitoid is affected by many factors such as size of experimental arena, tested densities, time duration of experiments, distribution of hosts, the possibility of searching parasitoids to leave the experimental units and number of parasitoids searching together (Islam et al 2006). Moreover, the foraging behaviour under field conditions is determined by many other factors namely host patch accessibility or distribution, presence of competitors and temperature (Fernández-arhex and Corley 2003;Luna et al 2007).…”
Section: Host Densitymentioning
confidence: 99%
“…on its host Callosobruchus chinensis and Islam (2002) reported that the developmental time of D. basalis on C. maculatus was 12-13 days at a constant temperature of 30±1°C. The present result is similar to that finding.…”
Section: Discussionmentioning
confidence: 99%
“…Under traditional storage conditions, 100% infestation of cowpea occurring within 3-5 months of storage is common (Booker 1967, Caswell 1981. Pulses are important sources of proteins, fats, carbohydrates, sugars, vitamin B and minerals, which considered as a poor men meat (Islam et al 2006).…”
Section: Introductionmentioning
confidence: 99%